Sulcus nervi dorsalis penis/clitoridis: its reliability as a character for sex determination of isolated human pubic bones - Nanka, O; Sedý, J; Jarolím, L (Prague medical report, 2007)
This study describes a distinct groove on the caudal and ventral surfaces of the pubic bone termed the "sulcus nervi dorsalis penis/clitoridis" and assesses its usefulness as a character for sex determination of isolated pubic bones. Analysis of 168 male and 118 female pubic bones showed that the presence of a sulcus was a non-random event. A sulcus was present in 72% of male pubic bones and 83% of female pubic bones examined (Czech population). Seven characters (including three of the sulcus) were measured in a sample of an 86 isolated pelvises grouped according to the gender. A step-wise discriminant function analysis was performed on this dataset to assess whether a combination of these characters could be used for gender identification of isolated pubic bones. A bivariate plot using Mahalanobis distances showed distinct differences in male and female pubic bones. The width of the sulcus and the craniocaudal length of the pubic symphysis significantly described most of the variations observed between male and female pelvises. A post hoc analysis of the reliability of the technique showed that stepwise discriminant function correctly identified 83% of male and 86% of female known-sex pelves. Thus discriminant function analysis of the sulcus and pubic bones can reliably be used to determine sex in human osseal remnants.
Keywords: klitoris; Sex Characteristics; lidé; penis; os pubis; mužské pohlaví; Female; Male; soudní antropologie; Penis; Pubic Bone; Clitoris; pohlavní dimorfismus; ženské pohlaví; Forensic Anthropology; Humans